2020
DOI: 10.3390/pharmaceutics12100963
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Choroid Plexuses for Protein Drug Delivery

Abstract: Delivery of therapeutic agents to the central nervous system is challenged by the barriers in place to regulate brain homeostasis. This is especially true for protein therapeutics. Targeting the barrier formed by the choroid plexuses at the interfaces of the systemic circulation and ventricular system may be a surrogate brain delivery strategy to circumvent the blood-brain barrier. Heterogenous cell populations located at the choroid plexuses provide diverse functions in regulating the exchange of material wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 229 publications
0
16
0
Order By: Relevance
“…Evidence that the choroid plexus plays a central role not only in regulation of the microenvironment of the central nervous system by secreting most of the cerebrospinal fluid (CSF) 1,2 but also in adjustment of the circadian rhythm 3 is accumulating. Accordingly, it is reasonable to consider that damage to the choroid plexus induces brain dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence that the choroid plexus plays a central role not only in regulation of the microenvironment of the central nervous system by secreting most of the cerebrospinal fluid (CSF) 1,2 but also in adjustment of the circadian rhythm 3 is accumulating. Accordingly, it is reasonable to consider that damage to the choroid plexus induces brain dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances that are beyond the scope of this review and were not covered include peptide- and ligand-mediated targeting of the ChP [ 150 , 151 ]. Recombinant proenzymes and antibodies can be delivered by I.C.V.…”
Section: Discussionmentioning
confidence: 99%
“…Next to targeting the mostly studied BBB, it was recently suggested that targeting other brain barriers such as the blood–CSF barrier might have added value in CNS drug delivery [ 25 , 26 ]. The blood–CSF barrier is located at the choroid plexus (CP) tissue, a cauliflower-like structure projecting into the four brain ventricles.…”
Section: Barriers In Brain Drug Deliverymentioning
confidence: 99%
“…Overall, detailed studies are needed to characterize the transport mechanisms at the blood–CSF barrier. Furthermore, the influence of factors such as CSF clearance flow rate and other cell layers to overcome (e.g., the ependymal cell layer lining the brain ventricles, the pia mater and glia limitans layers at the brain surface and the perivascular spaces) need to be further investigated [ 25 , 26 ]. It was for example reported that the pial membrane does not seem to impede molecule entry from CSF to the brain, while the dense network of glial cells in the glia limitans may slow down diffusion or be a site of accumulation [ 34 ].…”
Section: Barriers In Brain Drug Deliverymentioning
confidence: 99%